The policy trajectory of China’s globalizing Internet - Feng Yang; Shan Zhao; Xiaoqian Zhang (Digital Transformation and Society, 2022)
Purpose – China’s globalizing Internet describes a situation where China is using the Internet as a tool or medium to transmit its voice on the world stage and enhance its influence over the global Internet governance system and the global digitalization process. Several concerns, however, exist regarding China’s globalizing Internet strategies. This paper aims to respond to these concerns and enhance the understanding of China’s globalizing Internet strategies. Design/methodology/approach – This paper will use content analysis to trace the policy development trajectory of China’s globalizing Internet, including policy vision, policy-making agencies and policy tools. Findings – The Chinese government has issued a considerable number of policies to regulate and promote the development of the Internet since 2014. The key trend that emerged from the analysis of China’s globalizing Internet policy is the cooperation among different agencies. Existing policies have comprehensively used the supply-oriented tools, the environment-oriented tools and the demand-oriented tools; and the last two tools have been used more frequently in recent years. Originality/value – The analysis results contribute to understanding how China uses digital technology to enhance its influence over the global Internet governance system.